O ir e vir dos usuários nas unidades de saúde da família - Fernanda Marcelino de Rezende (2007)
The importance to understand why certain people frequently look for attention at the Unidades de Saúde da Família in Divinópolis and how the health professionals act facing the complaints presented are the object of this study. As theory references , were discussed the changing attempts for the health assistance model , which tries its organization from the implantation and expansion of the Unidades de Saúde da Família as strategy to improve the primary health attention. Physicians, nurses as well as assistant nurses were selected from the four earliest Family Health Staff in the municipal urban area. The subjects of the study were the people who attend the Unidades de Saúde da Família for three or more times during a month. To obtain these data, the Folhas de Controle Diário de Atendimento de Enfermagem, concerning to the months of March, April and May ,in 2006., were examined The field research was realized under the direct observation of the health professionals by means of semi-structured interview between them and the selected patients. It was chosen for this study a qualitative treatment in which the subjective conceptions and expressions were employed according to the Dialectic Historical Materialism and the discourse organization and analysis according to the Collective Subject Discourse under Lefèvre e Lefèvre (2005).The empirical material analysis made clear that the people enter the health services through a scheduled appointment, but most of them go to the health unities for free demand appointment, which causes the attendance to stand in serious conditions affecting the population. The reasons that lead people to the health unities are several ones: they can be noted from the necessity of scheduling an appointment to the necessity of finding there someone to talk to, to comfort them and help them to get out of routine. At their time, most of the professionals listen to these people , getting them rid of doubts , encouraging them to solve their problems. The ideas of reception, creation or strengthening of the link that exists between patients and professionals should be consolidated in order to provide an efficient attendance in spite of the difficulties found in a constant construction and reconstruction system